Pendidikan Agama Islam dan Pencegahan Dekadensi Moral: Studi Implementasi Pembentukan Karakter Peserta Didik di SMAN 1 Jati Agung Lampung Selatan - May Sheila Dwi Arianda br Purba; Nur Asiah; Beti Susilawati (WISE Pendidikan Indonesia, 2026)
Moral decline among students has become a critical issue in contemporary education, particularly amid the growing influence of social environments, peer interactions, and digital technology. This study aims to analyze the implementation of Islamic Religious Education in preventing students’ moral decline at SMAN 1 Jati Agung, South Lampung. Specifically, the study examines the planning of Islamic Religious Education implementation, teachers’ strategies for internalizing religious values, and the supporting and inhibiting factors influencing its implementation. This study employed a descriptive qualitative approach. The research was conducted at SMAN 1 Jati Agung, involving one Islamic Religious Education teacher and three Grade XI students as the main informants. Data were collected through semi-structured interviews, observation, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that Islamic Religious Education was implemented through structured lesson planning, religious habituation programs, teacher role modelling, personal approaches, classroom discussions, Qur’an reading literacy, congregational prayer, and socio-religious activities. The implementation was supported by school programs, teacher–student interaction, peer involvement, and the availability of worship facilities. However, several obstacles remained, including the limited moral awareness of some students, negative social influences, and the challenge of establishing a religious culture within a public school context. This study implies that Islamic Religious Education should be strengthened as a holistic character-building system involving teachers, schools, families, and the wider community to prevent students’ moral decline more effectively.